PENGARUH SOSIAL EKONOMI ISTRI TERHADAP TINGKAT FERTILITAS DI KOTA PEKANBARU - Agustia, Theresia; Harlen, Harlen; Rahmita, Rahmita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine how much influence the level of wife education, wife's wife status, wife's first marriage age, and the length of use of the wife's contraceptive device to the fertility level in Pekanbaru City. This research use sampling method then selected 100 person sample or respondent. The analysis method used in this research is multiple linear regression with SPSS 21.0 application. Based on the results of multiple linear regression test showed that fertility value in Pekanbaru City influenced by wife education level, wife work status, wife marriage age, and duration of contraceptive usage. The simultaneous regression coefficient (F test) shows that overall independent variable, wife education level (X1), wife's wife status (X2), wife's first marriage age (X3), and length of wife contraceptive use (X4) have significant effect to variable bound fertility (Y) in Pekanbaru City as evidenced by the value of F arithmetic greater than F table. From t test result partially indicate that t count of wife education level, wife work status, wife marriage age, and duration of wife contraception use significantly influence to fertility proved with probability value t count smaller than significant level.Keywords : Fertility, Level of Wife Education, Wife's Working Status, Wife's First Marriage, and Old Use of Wife's Contraception